Adjuvant therapy for pancreas cancer in an era of value based cancer care. (January 2016) - Ahn, Daniel H.; Williams, Terence M.; Goldstein, Daniel A.; El-Rayes, Bassel; Bekaii-Saab, Tanios
Highlights: Adjuvant therapy improves patient outcomes in resected pancreas cancer. Subgroups thought to benefit from radiation have similar outcomes with chemotherapy. Radiation is associated with increased cost, toxicities and uncertain added benefit. Modern radiotherapy and novel therapies may improve outcomes in pancreas cancer. Abstract: In resected pancreas cancer, adjuvant therapy improves outcomes and is considered the standard of care for patients who recover sufficiently post operatively. Chemotherapy or combined chemotherapy and radiation therapy (chemoradiation; CRT) are strategies used in the adjuvant setting. However, there is a lack of evidence to suggest whether the addition of RT to chemotherapy translates to an improvement in clinical outcomes. This is true even when accounting for the subset of patients with a higher risk for recurrence, such as those with R1 and lymph node positive disease. When considering the direct and indirect costs, impact on quality of life and questionable added clinical benefit, the true "net health benefit" from added RT to chemotherapy becomes more uncertain. Future directions, including the utilization of modern RT, integration of novel therapies, and intensifying chemotherapy regimens may improve outcomes in resected pancreas cancer.